A novel comprehensive macroscopic model for time-dependent vehicle routing problem with multi-alternative graph to reduce fuel consumption: A case study. (September 2016) - Alinaghian, Mehdi; Naderipour, Mansoureh
Graphical abstract: Diagram of the emission factor changes. Highlights: A comprehensive macroscopic model to reduce the fuel consumption is presented. Multi-alternative graph for green time-dependent routing problem is considered. Several traffic patterns and the ''first-in–first-out'' property is considered. A Modified Metaheuristic algorithm based on Gaussian Firefly algorithm is developed. One of the distribution companies in Iran is selected as a case study. Abstract: Vehicle routing problem (VRP) has attracted the attention of many researchers in recent years, but in spite of its application, researchers have shown little interest in the time-dependent vehicle routing problem. In recent years, much attention has been paid to the reduction of environmental emissions and reduction of fuel consumption. In this paper, the factors effective in the fuel consumption in time-dependent vehicle routing have been comprehensively studied and by considering factors such as load, vehicle speed, road gradient, and urban traffic, a novel comprehensive macroscopic model is presented to calculate fuel consumption in time-dependent vehicle routing problem. Additionally, the multi-alternative graph which enjoys great importance in time-dependent routing problem is also considered in the model presented. With regard to the issue that proposed problem belongs to the class of NP-hard problems, to find suitable routes with the least fuel consumption, an improved algorithm based on Gaussian Firefly algorithm is proposed. The results obtained from the proposed algorithm in comparison to Gaussian and basic Firefly algorithms show the appropriate performance of the suggested algorithm. Ultimately, one of the distribution companies in one of the cities of Iran (Esfahan) is studied as a case study.